Design and Simulation of an Automatic Temperature-Based Air Conditioner Control System Using ATmega16 - Aldrin Julianda Putra; Dwi Titi Maesaroh; Didi Susilo Budi Utomo (Lembaga Pengembangan Kinerja Dosen, 2026)
Technology is developing rapidly, especially in the field of electronics. One of its applications is a microcontroller-based automatic control system to improve efficiency and comfort in room temperature regulation. This study aims to design and simulate an automatic air conditioning control system based on temperature using the ATmega16 microcontroller. The LM35 sensor is used to measure room temperature, and the data is processed by the ATmega16 through its internal ADC feature. The measured temperature is displayed on a 16x2 LCD, and the system activates or deactivates the AC through a relay circuit according to predefined temperature thresholds. The research method includes circuit design using Proteus and programming with Microchip Studio. Based on simulation results, the system can accurately read temperature values and control the AC automatically according to the set conditions. These results indicate that the designed system works properly and has potential as a microcontroller-based automatic air conditioning control solution.